2023
DOI: 10.1084/jem.20220964
|View full text |Cite
|
Sign up to set email alerts
|

B cell receptor ligation induces IgE plasma cell elimination

Abstract: The proper regulation of IgE production safeguards against allergic disease, highlighting the importance of mechanisms that restrict IgE plasma cell (PC) survival. IgE PCs have unusually high surface B cell receptor (BCR) expression, yet the functional consequences of ligating this receptor are unknown. Here, we found that BCR ligation induced BCR signaling in IgE PCs followed by their elimination. In cell culture, exposure of IgE PCs to cognate antigen or anti-BCR antibodies induced apoptosis. IgE PC depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Two studies suggest limited antigen‐specific IgE titer change in pollen allergic individuals over a four‐month period with dupilumab alone, which would instead indicate persistent IgE + ASC cause pollen allergy 179,180 . Intriguingly, in one of those studies, patients concomitantly undergoing subcutaneous immunotherapy had IgE titres that dropped 50%–60%, 179 arguing putatively persistent IgE + ASC were being killed by exposure to cognate antigen, as would be predicted from a recent mouse study where IgE BCR ligation was shown to cause IgE + ASC apoptosis 181 . Additional human studies point to a long‐lived IgE + ASC population by showing IgE titer maintenance in periods of allergen avoidance, 182 but it is possible that without IL‐4R blockade IgE + ASC production occurs constantly from GC or mBC.…”
Section: The Life Spans Of Ige+ Ascmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies suggest limited antigen‐specific IgE titer change in pollen allergic individuals over a four‐month period with dupilumab alone, which would instead indicate persistent IgE + ASC cause pollen allergy 179,180 . Intriguingly, in one of those studies, patients concomitantly undergoing subcutaneous immunotherapy had IgE titres that dropped 50%–60%, 179 arguing putatively persistent IgE + ASC were being killed by exposure to cognate antigen, as would be predicted from a recent mouse study where IgE BCR ligation was shown to cause IgE + ASC apoptosis 181 . Additional human studies point to a long‐lived IgE + ASC population by showing IgE titer maintenance in periods of allergen avoidance, 182 but it is possible that without IL‐4R blockade IgE + ASC production occurs constantly from GC or mBC.…”
Section: The Life Spans Of Ige+ Ascmentioning
confidence: 99%
“…179,180 Intriguingly, in one of those studies, patients concomitantly undergoing subcutaneous immunotherapy had IgE titres that dropped 50%-60%, 179 arguing putatively persistent IgE + ASC were being killed by exposure to cognate antigen, as would be predicted from a recent mouse study where IgE BCR ligation was shown to cause IgE + ASC apoptosis. 181 Additional human studies point to a long-lived IgE + ASC population by showing IgE titer maintenance in periods of allergen avoidance, 182 but it is possible that without F I G U R E 4 Potential pathways to IgE production in mice and humans. IgE class-switch recombination (CSR) may occur during (1) the preGC phase of a B cell response, to give rise to IgE + preGC B cells, which go on to become short-lived extrafollicular IgE + ASC.…”
Section: The Life S Pan S Of I G E + a Scmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we have since learned more about mechanisms which uniquely restrict IgE and not IgG1 responses (e.g. IL-21) 7,32,33 , exposing that IgE and IgG1 may be less tightly linked than once thought. Furthermore, it is generally assumed that the rate at which switch remnants are identified represents the minimal possible contribution of IgG1 intermediaries given that only a portion of switching events leave these remnants 31 .…”
Section: Sequential Switching Through Igg1 Is Redundant For Memory Ig...mentioning
confidence: 99%